Mapping the Regional Distribution of Theatre in Denmark. Three Different Approaches Based on Official Theatre Statistics - Hansen, Louise Ejgod (Nordic Theatre Studies, 2015)
This article presents three different mappings of the regional distribution of theatre in Denmark. Together, the three mappings cover important aspects of a national theatre system: production (subsidy), distribution of performances and theatre consumption. All of them are based on official theatre statistics and should, as such, be considered authoritative credible mappings on which a cultural policy debate on the decentralization of theatre in Denmark could be based. However, the article demonstrates that the three different mappings result in three different results regarding the regional distribution of theatre in Denmark. This adds complexity to the policy debates because no definite conclusions can be made. In addition, the methodological discussion in the article demonstrates that the existing data sets have severe limitations.